The future of sport tourism in Sarawak - Bong, Nyat Nee (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study aims to find out the future potential of the sport-based tourism to be promoted as an attraction in sarawak's tourism industry. This study only focuses on the demand side of the industry